2010
DOI: 10.1080/19439341003599726
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous impact of the social programme Oportunidades on use of contraceptive methods by young adult women living in rural areas

Abstract: Rarely have researchers explored the distribution of a programme's effects in a population, tending to focus on unidimensional measures of impact instead. This can mask heterogeneity of effects, making it difficult to identify subsets of the population for whom impacts might differ from a population average. The authors exploit the design of Mexico's Oportunidades programme to construct measures of the heterogeneous impacts of the programme on contraception and compare these with conventional effect estimates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…We used a self-reported measure of Oportunidades exposure, and data were not available on length of program exposure; previous research among beneficiaries reported mixed results by length of exposure. 28,48 Women in our sample were asked about current exposure, so our measure may not have captured those who had been exposed, but left the program. We restricted our pregnancy models to women aged 15–19 to avoid including any pregnancies that could have occurred prior to program inclusion in 1998 or 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a self-reported measure of Oportunidades exposure, and data were not available on length of program exposure; previous research among beneficiaries reported mixed results by length of exposure. 28,48 Women in our sample were asked about current exposure, so our measure may not have captured those who had been exposed, but left the program. We restricted our pregnancy models to women aged 15–19 to avoid including any pregnancies that could have occurred prior to program inclusion in 1998 or 2000.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of data from Oportunidades’ experimental period, contraceptive use was higher among female heads of household exposed to the program than among their unexposed counterparts, 2,11 with greater change among the poorest women than among wealthier women; 48 no link was found between birth spacing and program exposure between 1998 and 2003. 2 One study reported a negative impact on pregnancy and childbirth among women younger than 20 during the short-term follow-up experimental period (1998–2000), although the finding was nonsignificant after controlling for education.…”
Section: Mexico’s Oportunidades Programmentioning
confidence: 98%
“…When comparing women enrolled in the programme for six years with those enrolled for four years there was no significant difference, however, suggesting a flattening trend of the impact. Lamadrid-Figueroa et al (2010) further disaggregate the effects and find a markedly larger programme impact on contraceptive use for the poorest of the poor (a 25-40 percentage point increase) that can be attributed to Oportunidades. They hypothesise that it could be the case that the poorest subjects felt more compelled to attend the health talks in order to retain the benefits of the programme or, alternatively, that the very poorest group may have been the most marginalised with regards to knowledge about contraceptive practices.…”
Section: Journal Of Developmentmentioning
confidence: 96%
“…Further, economically insecure women may engage in high-risk sexual behavior to procure money, food, or other goods [610]. In addition to these observational data, experimental evidence supports the hypothesis that economic interventions can improve reproductive health [1114]. …”
Section: Introductionmentioning
confidence: 95%